Eomes Expression Defines Group 1 Innate Lymphoid Cells During Metastasis in Human and Mouse - Verma, Riva; Er, Jun Zhi; Pu, Ren Wei; Sheik Mohamed, Jameelah; Soo, Ross A.; Muthiah, Harish Mithiran; Tam, John Kit Chung; Ding, Jeak Ling (Frontiers in Immunology, 2020)
Recent studies have attempted to uncover the role of Group 1 Innate lymphoid cells (ILCs) in multiple physiological contexts, including cancer. However, the definition and precise contribution of Group 1 ILCs (constituting ILC1 and NK subsets) to metastasis is unclear due to the lack of well-defined cell markers. Here, we first identified ILC1 and NK cells in NSCLC patient blood and differentiated them based on the expression of transcription factors, T-bet and Eomes. Interestingly, Eomes downregulation in the peripheral blood NK cells of NSCLC patients positively correlated with disease progression. Additionally, we noted higher Eomes expression in NK cells (T-bet+Eomeshi) compared to ILC1s (T-bet+Eomeslo). We asked whether the decrease in Eomes was associated with the conversion of NK cells into ILC1 using Eomes as a reliable marker to differentiate ILC1s from NK cells. Utilising a murine model of experimental metastasis, we observed an association between increase in metastasis and Eomes downregulation in NKp46+NK1.1+ Group 1 ILCs, which was consistent to that of human NSCLC samples. Further confirmation of this trend was achieved by flow cytometry, which identified tissue-specific Eomeslo ILC1-like and Eomeshi NK-like subsets in the murine metastatic lung based on cell surface markers and adoptive transfer experiments. Next, functional characterization of these cell subsets showed reduced cytotoxicity and IFNγ production in Eomeslo ILC1s compared to Eomeshi cells, suggesting that lower Eomes levels are associated with poor cancer immunosurveillance by Group 1 ILCs. These findings provide novel insights into the regulation of Group 1 ILC subsets during metastasis, through the use of Eomes as a reliable marker to differentiate between NK and ILC1s.